STUDY OF DRUG PRESCRIPTION PATTERN AND SAFETY OF DIFFERENT DRUGS USED IN ALCOHOL-RELATED CHRONIC LIVER DISEASE IN GSVM COLLEGE, KANPUR: A TERTIARY CARE HOSPITAL - Dr Vekaria Harsh Mansukhbhai; Dr Virendra Kushwah; Dr Pooja Agrawal; Dr Ajesh Chandra Gupta; Dr Amit Kumar; Dr Himanshu Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Management of alcohol-related chronic liver disease involves a multifaceted approach, including lifestyle modification, abstinence from alcohol, and pharmacotherapy. Despite the availability of various treatments, there is a lack of consensus on the optimal drug regimen and a need for localized data on drug prescription patterns and their safety profiles.Aims & Objectives: This study was planned to evaluate drug prescription pattern and safety of different drugs used in patients with alcohol-related chronic liver disease.Materials & Methods:  An observational prospective study was conducted by the Department of Pharmacology, in collaboration with the Department of Medicine, G.S.V.M. Medical College, Kanpur. Prescriptions were collected and further studied. All basic details and prescribed drugs were collected and entered in predesigned proforma.Results: The gender distribution indicated a significant male predominance (99.45%). The drug prescription pattern revealed an average of 6.67 drugs per prescription.Antibiotics were prescribed at 1.39 per encounter, with 65.08% prescribed using generic names and 90.14% sourced from government supplies. Number of drugs prescribed by generic name were 779 (65.08%) drugs and most according to essential list of medicines i.e., 80.86% which increases rationality of our prescription. In present study, causality assessment of ADRs according to Naranjo scale suggested that of total 19 patients who had ADRs, 22(43.14%) were probable and 29(56.86%) were possible.Conclusion: While the study provides a detailed snapshot of current practices and safety issues, ongoing efforts are required to enhance drug prescription practices and ensure the safest and most effective treatment strategies for patients with alcohol-related chronic liver disease.Further research is needed to refine drug prescription strategies, evaluate long-term outcomes, and explore the efficacy of emerging therapies.